2020
DOI: 10.15376/biores.15.3.5388-5401
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanocellulose addition to phenol-formaldehyde adhesive in water-resistant plywood manufacturing

Abstract: This study examined the effect of applying cellulose nanoparticles as a filling material for phenol-formaldehyde (PF) resin in the process of manufacturing water-resistant plywood. Based on investigations that concerned the rheological behavior of resin mixture containing various amounts of nanofiller, the modification of resin resulted in a major increase of viscosity. Although Fourier transform infrared spectroscopy did not fully explain the effect of modification on the chemical structure of the adhesive, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The results of the shear strength test, which is a commonly used indicator of adhesive behavior in plywood [66], are presented in Figure 5. Studies have shown that the effect of oak bark addition on the bonding quality of manufactured plywood depends on the share of filling additives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the shear strength test, which is a commonly used indicator of adhesive behavior in plywood [66], are presented in Figure 5. Studies have shown that the effect of oak bark addition on the bonding quality of manufactured plywood depends on the share of filling additives.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, levels of viscosity that are too high may indicate the occurrence of agglomerates made of filling particles. The fillers act as carriers of stress along the glue line, and concentrations of stress at certain points can lead to a weakening of bonding strength [66]. The shear strength of all manufactured plywood, regardless of the additive quantity and type, exceeded the value of 1.0 N/mm 2 required by EN 314-2 [68].…”
Section: Resultsmentioning
confidence: 99%
“…There are some interesting reports on using nanomaterials in UF adhesive to reduce formaldehyde release from the final products, that is, MDFs 27–31 . Cademartori et al reported alumina nanoparticles as a novel formaldehyde scavenger for UF resin.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nanocellulose has been increasingly studied for its many intriguing properties and immense potential. On the side of wood composites research, micro and nano brillated cellulose have been recently investigated as a ller for wood adhesives in particle boards (Mahrdt et al 2016;Hansted et al 2019; Morais Júnior et al 2020), OSB (Veigel et al 2011(Veigel et al , 2012, and plywood (Kawalerczyk et al 2020). Veigel et al (2011) studied the effect of the addition of CNF bers into UF for wood beams.…”
Section: Introductionmentioning
confidence: 99%
“…These results were determined to be due to the larger particle size when adding MFC, improving the adhesive availability for bonding with other particles. Recently, Kawalerczyk et al 2020, studied the effect of CNC addition on plywood panels to react with phenol formaldehyde (PF) resins. They found that 3 g of CNC to 100 g d.m.…”
Section: Introductionmentioning
confidence: 99%